Prevalence and factors associated with undernutrition among 15-49-year-old women in Sierra Leone: A secondary data analysis of Sierra Leone Demographic Health Survey of 2019. - Nelson Onira Alema; Eric Nzirakaindi Ikoona; Mame Awa Toure; Oliver Eleeza; Amon Njenga; John Bosco Matovu; Lucy Namulemo; Ronald Kaluya; Kassim Kamara; Freddy Wathum Drinkwater Oyat; Emmanuel Olal; Judith Aloyo; et al. (PLoS ONE)
Background Undernutrition of women of childbearing age is pertinent for maternal and offspring health. This study aimed to determine the prevalence and factors associated with undernutrition (underweight and stunting) among women of reproductive age (15-49 years) in Sierra Leone using a secondary data analysis of the 2019 Demographic Health Survey. Methods Anthropometric measurements and maternal characteristics were obtained from the Sierra Leone Demographic Health Survey (SLDHS) of 2019. The heights and weights of women were measured, and BMI in kg/m2 was calculated. Based on the World Health Organization's recommendations, stunting was defined as heights <145cm and being underweight as BMI <18.5kg/m2. Multivariate logistic regression analyses were conducted to identify factors associated with undernutrition, with a significant level set at p<0.05. Results A total of 7,514 women of reproductive age, 15-49 years were analyzed in this study. The prevalence of stunting and underweight were 1.5% (113/7514) and 6.7%(502/7,514), respectively. Women with primary education had a 47% lower likelihood of being stunted (adjusted Odds Ratio [aOR] = 0.53, 95% Confidence Interval [CI]:0.30-0.94;p = 0.029) than secondary education. Women in the poorest wealth index had a 51% lower likelihood of being stunted (aOR = 0.49,95%CI:0.27-0.88;p = 0.017) than the middle wealth index. Underweight was 1.48 times more likely among women with a parity of one-to-four (aOR = 1.48,95% CI:1.08-2.03;p = 0.015) than women who never gave birth. Also, underweight was 1.41 times more likely among women who listened to radios (aOR = 1.41,95% CI:1.14-1.74;p = 0.002) than those who did not. Age groups of 15-19 years and 40-49 years had a 54% (aOR = 0.46,95%CI:0.34-0.62;p<0.001) and 34% (aOR = 0.66,95%CI:0.45-0.97;p = 0.035) lower likelihood of being underweight than 20-29-year age group, respectively. Women with primary education had a 26% lower likelihood of being underweight (aOR = 0.74,95%CI:0.56-0.99;p = 0.042) than those with secondary education. However, none of the wealth indices was significantly associated with being underweight. Conclusion The prevalence of underweight and stunting among women of reproductive age (15-49 years) in Sierra Leone was lower than regional and world data. This study highlights similarities and differences in this population's prevalence and factors associated with undernutrition. Underweight and stunting were less likely in women with primary education, while parity of one to four and listening to radios were significantly associated with being underweight. Further trend studies using DHS data from 2010, 2014, and 2019 are warranted to understand the dynamics of undernutrition among women (15-49 years) in Sierra Leone.